1992
DOI: 10.1103/physreva.45.8693
|View full text |Cite
|
Sign up to set email alerts
|

Surface elastic and molecular-anchoring properties of nematic liquid crystals confined to cylindrical cavities

Abstract: The measurement of the saddle-splay surface elastic constant K~4 in a nernatic liquid crystal is reported based on two independent deuterium nuclear-magnetic-resonance ( H-NMR) experiments. Fifty years after the pioneering work of Oseen and Zocher, these measurements were made from observations of nematic director-field configurations and a configuration transition discovered in submicrometer-sized cylindrical cavities of Nuclepore membranes under selected surface preparations and wall curvatures. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(114 citation statements)
references
References 42 publications
2
108
0
4
Order By: Relevance
“…Such situation can take place for a planar surface orientation of a director in the plane normal to the porous axis [3]. Nevertheless, theory predicts the possibility of formation of different orientational configurations in the system under consideration [12,13], which are shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 98%
“…Such situation can take place for a planar surface orientation of a director in the plane normal to the porous axis [3]. Nevertheless, theory predicts the possibility of formation of different orientational configurations in the system under consideration [12,13], which are shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 98%
“…Crawford et al have investigated the molecularanchoring properties of the nematic LCs in cylindrical cavities and found that an escaped radial with singular point defects (ERPD) alignment was preferably supported for an untreated cavity with its radius larger than 50 nm. [ 50 ] We believe a similar alignment mechanism could happen inside the aperture. At the ERPD alignment inside the aperture, the effective refractive index of the LCs was approximated to be the same as the isotropic state for an unpolarized probe light.…”
Section: Op133mentioning
confidence: 84%
“…24 K is called the surface elastic constant because it is the coefficient of a divergence term which can be transformed to a surface integral by using Gauss theorem. This elastic constant has to be included because analysis of the Frank free energy for nematics confined to cylindrical regions indicates that the director pattern is dependent on the surface elastic constant K 24 if there is weak normal anchoring and escape along the cylinder axis (Crawford et al, 1992) 31 / KK   …”
Section: Nematic Configurationmentioning
confidence: 99%